Novel Interpositional Vein Grafting for Pedicle Extension of Island Pedicle Flaps - Yoshida, Shuhei; Koshima, Isao; Nagamatsu, Shogo; Yokota, Kazunori; Yamashita, Shuji; Harima, Mitsunobu; Tashiro, Kensuke (Journal of Reconstructive Microsurgery Open, 2018)
Background Island pedicle flaps often have the problem of limited reach. In such cases, free flaps are useful for reconstruction but often have the issue of unavailability of suitable recipient vessels. Therefore, it would be helpful if the pedicle of an island flap could be extended as far as necessary.Methods Here, we describe the use of interpositional vein grafts to extend island pedicle flaps for the reconstruction of an ischemic above-knee amputation stump in one case and to seal an intractable fistula on the buttock after radiation therapy in another case. In the patient with the ischemic stump, a deep inferior epigastric perforator flap was extended by 6 cm using the great saphenous vein harvested from the contralateral side, allowing successful coverage of the stump. In the patient with an intractable fistula on the buttock, a thoracodorsal artery and vein graft that was extended by 25 cm using the cephalic vein harvested from the right forearm to upper arm allowed successful sealing of the fistula.Results Circulation was satisfactory in both cases and both flaps survived. The operative procedure was straightforward.Conclusion Interpositional vein grafts may be a feasible option for the extension of island pedicle flaps to include the features of an island pedicle flap and a free flap.
Keywords: vein grafting; free flaps; island pedicle flaps